Pathology of the liver sinusoids1. Issue 7 (8th March 2014) - Brunt, Elizabeth M; Gouw, Annette S H; Hubscher, Stefan G; Tiniakos, Dina G; Bedossa, Pierre; Burt, Alastair D; Callea, Francesco; Clouston, Andrew D; Dienes, Hans P; Goodman, Zachary D; Roberts, Eve A; Roskams, Tania; et al.
<x xml:space="preserve">Abstract</x> The hepatic sinusoids comprise a complex of vascular conduits to transport blood from the porta hepatis to the inferior vena cava through the liver. Under normal conditions, portal venous and hepatic artery pressures are equalized within the sinusoids, oxygen and nutrients from the systemic circulation are delivered to the parenchymal cells and differentially distributed throughout the liver acini, and proteins of liver derivation are carried into the cardiac/systemic circulation. Liver sinusoid structures are lined by endothelial cells unique to their location, and Kupffer cells. Multifunctional hepatic stellate cells and various immune active cells are localized within the space of Disse between the sinusoid and the adjacent hepatocytes. Flow within the sinusoids can be compromised by physical or pressure blockage in their lumina as well as obstructive processes within the space of Disse. The intimate relationship of the liver sinusoids to neighbouring hepatocytes is a significant factor affecting the health of hepatocytes, or transmission of the effects of injury within the sinusoidal space. Pathologists should recognize several patterns of injury involving the sinusoids and surrounding hepatocytes. In this review, injury, alterations and accumulations within the liver sinusoids are illustrated and discussed.